Chapter Lingua... di che genere? Riflessioni preliminari e proposte operative per una comunicazione istituzionale universitaria che superi il binarismo di genere - Pepponi, Elena (Proceedings e report, 2023)
The main object of this work is the relationship between non-binary people and institutional communication, the laCer being mostly conceived to represent only two genders, masculine and feminine. Starting from the origin on gendered language in Italian institutional communication, an overview about actual strategies of binary inclusion will be given. Furthermore, the paper will analyse some possible new strategies suggested to implement inclusion in a non-binary perspective. The aim of this paper is to lay the foundation for further work and to improve the development of collective guidelines to write institutional texts able to represent all the complex gender identities that are present in nowadays societies.